PRODUCTION AND COSTABILITY ANALYSIS OF BIOACTIVE HYDROLYZATES OF WHEY PROTEIN - Slavica ARSIC; Predrag VUKOVIC; Nataša KLJAJIC; Marice RAKIN; Gordana KOKEZA; Maja BULATOVIC (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Due to the fact that individual whey proteins have their own unique nutritional, functional and biological characteristics, the latest research in this area draws attention to the possibility of synthesizing a wide range of bioactive compounds derived from whey proteins. There are various ways to release bioactive peptides from precursor proteins or whey parent proteins. The paper will present the production of bioactive whey protein hydrolyzates (BHPS), which exhibit high antioxidant activity, and their economic profitability of production. Research is focused on the enzymatic and microbiological process of modifying whey proteins. Whey proteins can be easily modified under mild conditions of temperature and Ph values. For the purpose of this research, two scenarios were modeled: Scenario A, which involves the use of whey, and Scenario B, which involves the use of whey protein concentrate as a protein source. The entire process for both scenarios, which includes pre-treatment, whey protein modification and product separation, was modeled using the SuperPro Desinger program, which is equipped with a wide range of processes, and can be used for mathematical evaluation of the economic performance of the process.